2019
DOI: 10.1111/ijcp.13313
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of good glycaemic control is challenging – A cohort study of type 2 diabetes patient in North Karelia, Finland

Abstract: Summary Aims This study assessed type 2 diabetes treatment outcomes and process indicators using a comprehensive type 2 diabetes patient cohort in North Karelia, Finland, from 2011 to 2016. Methods Data from all diagnosed type 2 diabetes patients (n = 8429) living in North Karelia were collated retrospectively from regional electronic patient records. We assessed whether HbA1c and low‐density lipoprotein (LDL) were measured and managed as recommended. Results The HbA1c measurement rate improved (78% vs 89%) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 30 publications
(41 reference statements)
1
11
1
Order By: Relevance
“…The estimated yearly increase of 0.84 mmol/mol (12*0.07 mmol/mol, 0.08% units) in average HbA1c levels observed in this study until the policy change at the beginning of 2017 is a bit over the magnitude of the estimated increase of 0.75 mmol/mol (0.07% units in HbA1c) per year that was observed in our previous study among the same population in 2011-2016 [33]. The small differences in results are due to differences in densities of follow-up (monthly level in the current study vs. yearly level in the paper by Nazu et al (2019)) in addition to differences in lengths of follow-up [33]. In the current study, an additional, immediate increase of 0.81 mmol/mol (0.08%) was detected at the time of the policy change in the current study.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The estimated yearly increase of 0.84 mmol/mol (12*0.07 mmol/mol, 0.08% units) in average HbA1c levels observed in this study until the policy change at the beginning of 2017 is a bit over the magnitude of the estimated increase of 0.75 mmol/mol (0.07% units in HbA1c) per year that was observed in our previous study among the same population in 2011-2016 [33]. The small differences in results are due to differences in densities of follow-up (monthly level in the current study vs. yearly level in the paper by Nazu et al (2019)) in addition to differences in lengths of follow-up [33]. In the current study, an additional, immediate increase of 0.81 mmol/mol (0.08%) was detected at the time of the policy change in the current study.…”
Section: Discussionsupporting
confidence: 51%
“…It should be noted that all the patients included in our study were diagnosed with T2D at least 1 year before the start of the follow-up of HbA1c development and at least 4 years before the policy change in Jan, 2017. In addition, according to our previous study, younger patients with T2D were poorly monitored compared with the older patients in the North Karelia region [33]. Furthermore, we did not have information on patients using private health care services.…”
Section: Discussionmentioning
confidence: 97%
“…Successful change requires new roles and responsibilities, and willingness among healthcare professionals to co-work and co-learn [ 34 , 35 ]. In Siun sote, the quality improvement of type 2 diabetes care has been active, and the quality of type 2 diabetes care at the primary-health care level has been shown to be very good [ 36 ], but there is always room for improvement.…”
Section: Discussionmentioning
confidence: 99%
“…In North Karelia, the amount of statin prescriptions for type 2 diabetes patients increased more among men than women during the follow-up period, and this might at least partly explain the lower levels of LDL values for men. In general, the achievements of LDL targets were moderately good and our previous study showed that 59% of women and 66% of men achieved the recommended level of LDL (≤2.5 mmol/l) in 2015–2016 [ 42 ]. In addition, a subgroup analysis of type 2 diabetes patients with CVD indicated that 22% of women and 32% of men achieved the LDL target < 1.8 mmol/l.…”
Section: Discussionmentioning
confidence: 99%